Bibliometric Analysis of Zakat Research in Scopus Database - Muhsin Nor Paizin; Siti Maziah Ab Rahman; Khalid Abdul Wahid; Mohd Noor Azam Nafi; Suryani Awang; Mariam Setapa (International Journal of Zakat, 2021)
Scopus research paper on the zakat was systematically analyzed using the VOSviewer bibliometric measurement. A total of 492 citation data was exported from Scopus on the query of Zakat, and from the initial result, twelve journals were selected in the expanded query process. The journals are Journal of Islamic Accounting and Business Research, International Journal of Islamic and Middle Eastern Finance and Management, International Journal of Innovation Creativity and Change, Advanced Science Letters, and Iop Conference Series Earth and Environmental Science were selected in the query expansion and exported for data visualization in VOSviewer. Results from the journal query returned 492 documents specializing in research of zakat payment. Co-word or co-occurrence analysis was used to identify key themes, and potential future research direction was highlighted.